RISING DRUG ADDICTION IN J & K: CAUSES, EFFECTS, AND WAY FORWARD - Ahmad Wani, Mushtaq (International Journal of Psychosocial Rehabilitation, 2025)
The Jammu and Kashmir state is one of the most important states across India, which has been gifted with innumerable blessings, and one of the precious blessings is the multitalented young and educated youth. Many multi-talented young and educated youth of Jammu and Kashmir have earned name and fame in various fields all across the world. The young, educated youth of Jammu and Kashmir have immense potential and talent and are a precious asset to the society. However, for the last two decades, there has been a sharp surge of social issues and evils in Jammu and Kashmir. The most burning social issues and evils facing Jammu and Kashmir are drug abuse, suicides, domestic violence, acid attacks, robbery, theft, etc. Drug abuse is the most dangerous social issue and evil because it has consumed thousands of young, educated youth and ruined thousands of families all across the state. Drug addiction is not just a health issue but also a socioeconomic and humanitarian crisis. Drug addiction is the mother of many evils in Jammu and Kashmir that demands immediate and comprehensive attention and action for the peaceful and prosperous Jammu and Kashmir.